Evaluating the kinetic basis of plant growth from organs to ecosystems. Issue 1 (16th February 2018) - Michaletz, Sean T.
Abstract : Contents   Summary 37 I. Introduction 37 II. Predictions for metabolic kinetics 38 III. Kinetics of net photosynthesis 38 IV. Kinetics of plant growth 40 V. Hypotheses for higher‐level kinetic decoupling 41 VI. Conclusions 42   Acknowledgements 42   References 42 Summary: Understanding how temperature influences the scaling of physiological rates through levels of biological organization is critical for predicting plant responses to climate. Metabolic theory predicts that many rates increase exponentially with temperature following an activation energy ( E ) of 0.32 eV for photosynthesis. Here, I evaluate this prediction for net photosynthesis and organ, individual, and ecosystem growth. Observed E for photosynthesis varied widely but was not statistically different from predictions, while E for organs was greater than predicted, and E for individuals and ecosystems only weakly characterized temperature responses. I review several hypotheses that may underlie these results. Understanding how multiple rate‐limiting processes coalesce into a single E that characterizes metabolic responses to temperature, and how to best estimate E from unimodal data, remain important challenges. Abstract : Editorial byLennon & Dolan, 219 : 5 .